Association between dehydroepiandrosterone-sulfate and attention in long-term survivors of childhood acute lymphoblastic leukemia treated with only chemotherapy. (February 2017) - Cheung, Yin Ting; Chemaitilly, Wassim; Mulrooney, Daniel A.; Brinkman, Tara M.; Liu, Wei; Banerjee, Pia; Srivastava, Deokumar; Pui, Ching-Hon; Robison, Leslie L.; Hudson, Melissa M.; Krull, Kevin R.
Highlights: Childhood acute lymphoblastic leukemia (ALL) survivors have endocrine complications. Male survivors with low dehydroepiandrosterone-sulfate (DHEAS) had worse attention. Partial adrenal insufficiency may impact neurocognitive function in ALL survivors. Males may be more vulnerable to neurocognitive effects of low DHEAS than females. Abstract: Long-term survivors of childhood acute lymphoblastic leukemia (ALL) are at risk for neurocognitive impairment, as well as compromised hypothalamic-pituitary-adrenal (HPA) function. Dehydroepiandrosterone-sulfate (DHEAS) is an adrenal androgen commonly used as a marker of HPA function. In the general population, a low level of DHEAS has been associated with poorer cognition. At ≥2 years post-treatment, we examined the association of DHEAS with attention outcomes in 35 male and 34 female long-term survivors of childhood ALL (mean[standard deviation] age at evaluation 14.5[4.7] years; 7.5[1.9] years post-diagnosis) who were treated with only chemotherapy and without prophylactic cranial irradiation. Male survivors with low-normal levels of DHEAS had worse performance than male survivors with high levels of DHEAS on multiple measures of attention (all P 's < 0.05). However, association between DHEAS and attention measures were not found in female survivors. Our results suggest that survivors of ALL who suffer from partial but persistent adrenal insufficiency may be at risk for neurocognitive deficits. This finding should be validated in a larger prospective study, with attention to sex differences in the potential impact of adrenal insufficiency on neurocognitive outcomes.